(untitled) (Journal of Pakistan Orthopaedic Association, 2013)
Objective: To determine the effectiveness of local steroid injections in the management of plantar fasciitis in comparison with conventional treatment with analgesics. Material and Method: This prospective hospital based randomized control study was conducted in the Department of Orthopedics and Spine Surgery, Post Graduate Medical Institute, Hayatabad Medical Complex, Peshawar from July 2010 to January 2011 on 52 patient of either sex. The patients were divided into two treatment groups. After assigning the subjects randomly between the groups by lottery method, treatment was applied and pain was noted at 1st, 3rd and 5th week after treatment. Results: The study was conducted on 52 patients of plantar fasciitis. In which male to female ratio was 1:1.73. Average age was 44.11 years+ 9.76SD. Majority of patients were at the age group of 31-45 years. Pain at 1st, 3rd and 5th week was significant in both the groups with p-value 0.000, 0.000 and 0.000 respectively. Conclusion: Local steroid injection along with conventional treatment is better than conventional treatment. Key word: Steroid, Plantar Fasciitis, Calcaneum, Tenderness